2008
DOI: 10.1038/sj.cgt.7701121
|View full text |Cite
|
Sign up to set email alerts
|

An efficient liposomal gene delivery vehicle using Sendai F/HN proteins and protamine

Abstract: By means of a simple mixing procedure, we have constructed cationic Sendai virosomes consisting of fusogenic viral F/HN proteins and cationic lipids. Sendai virus F/HN proteins were purified by Triton X-100 treatment and sequential centrifugation, and then quantitatively added to cationic liposomes. The presence of HN proteins is essential for hemolytic activity of Sendai virus as well as efficient gene transfection. The amount of detergent added for purification of F/HN proteins was also crucial for hemolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…This is especially important for the delivery of more labile drugs like genes and peptides. The use of cationic lipids and polymers for intracellular drug delivery by facilitating endosomal escape is well documented 131 . Lipids such as DOTMA and DOTAP as well as branched polymers like polyethyleneimine and PAMAM dendrimers have been used extensively for their ability to fuse with the endosomal membrane thus dispelling their contents into the cytoplasm 132 .…”
Section: Biological Barriersmentioning
confidence: 99%
“…This is especially important for the delivery of more labile drugs like genes and peptides. The use of cationic lipids and polymers for intracellular drug delivery by facilitating endosomal escape is well documented 131 . Lipids such as DOTMA and DOTAP as well as branched polymers like polyethyleneimine and PAMAM dendrimers have been used extensively for their ability to fuse with the endosomal membrane thus dispelling their contents into the cytoplasm 132 .…”
Section: Biological Barriersmentioning
confidence: 99%
“…Taken into account this point, we selected chitosan nanoparticles, a non-viral vector, in the present study. Non-viral vectors include liposomes [7][8][9] , composites [10] , microspheres [11] , and nanoparticles [12,13] , but the cytotoxicity of the liposomes limits its application in vivo. Owing to its loose constitution, the constancy of composites is poor.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it should be emphasized that Bombelli et al and Kim et al observed a similar correlation between transfection efficiency and extent of DNA condensation, using cationic gemini surfactants and protamine, respectively, as DNA condensing agents [40,41]. On the other hand, Farago et al reported an inverse correlation between the packaging of CL/DNA complexes and their transfection efficiency using multivalent cationic lipids [42].…”
Section: Discussionmentioning
confidence: 84%